Crystal engineering of TMPOx-coated LiNi0.5Mn1.5O4 cathodes for high-performance lithium-ion batteries. (October 2020) - Kuenzel, Matthias; Kim, Guk-Tae; Zarrabeitia, Maider; Lin, Shawn D.; Schuer, Annika R.; Geiger, Dorin; Kaiser, Ute; Bresser, Dominic; Passerini, Stefano
Graphical abstract: Abstract: The use of cobalt-free LiNi0.5 Mn1.5 O4 (LNMO) would provide a great leap forward towards the realization of sustainable lithium-ion batteries. However, the high operating voltage remains to be a great challenge for the cathode/electrolyte stability. Herein, we report a rational material design to address these challenges by carefully tuning the synthesis parameters in order to engineer LNMO crystals with tailored surface facets, providing an exceptional rate capability and improved interfacial stability. The additional introduction of protective TMPOx coatings further enhances the long-term cycling stability, in particular, at elevated cut-off potentials up to 4.95 V, increased temperature of 40 °C, and high dis-/charge rates. As a result of the careful design of the LNMO active material particles, lithium-ion cells employing this material together with Li4 Ti5 O12 anodes provide an excellent rate capability with 80% of the low-rate capacity at fast dis-/charge rates of 10C combined with highly stable cycling at such high rate, as highlighted by a capacity fading of less than 5% after 1000 cycles.